1971
DOI: 10.3181/00379727-137-35794
|View full text |Cite
|
Sign up to set email alerts
|

Phenothiazine-Induced Hyperglycemia: Relation to CNS and Adrenal Effects

Abstract: An increase in blood glucose levels after the administration of chlorpromazine has been observed in several animal species including man (1-5). Other phenothiazines have been shown to exhibiit a hyperglycemic response when administered to rats (6). Neither a depression of the motor activity nor a reduced body temperature are decisive factors in the origin of the chlorpromazineinduced hyperglycemia ( 7 ) .Phenothliazine derivatives have been shown to release catecholamines from adrenal glands in vitro (8). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

1976
1976
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 3 publications
0
9
0
1
Order By: Relevance
“…Medications have been implicated as potentially impairing glucose metabolism include centrally acting α blockers, β blockers, corticosteroids, cyclosporine, phenytoin, phenothiazines, thiazide diuretics, and oral contraceptives containing norgestrel (28,(31)(32)(33)(34)(35)(36). Valproate has been found to induce a metabolic syndrome characterized by centripetal obesity, hyperinsulinemia, lipid abnormalities, polycystic ovaries, and hyperandrogenism in women with epilepsy (37,38).…”
Section: (Am J Psychiatry 2000; 157:975-981)mentioning
confidence: 99%
“…Medications have been implicated as potentially impairing glucose metabolism include centrally acting α blockers, β blockers, corticosteroids, cyclosporine, phenytoin, phenothiazines, thiazide diuretics, and oral contraceptives containing norgestrel (28,(31)(32)(33)(34)(35)(36). Valproate has been found to induce a metabolic syndrome characterized by centripetal obesity, hyperinsulinemia, lipid abnormalities, polycystic ovaries, and hyperandrogenism in women with epilepsy (37,38).…”
Section: (Am J Psychiatry 2000; 157:975-981)mentioning
confidence: 99%
“…[38][39][40] The earlier case literature has also associated some conventional antipsychotics with type 2 diabetes. [41][42][43] Prospective trials involving relatively small numbers of schizophrenia patients have also examined the association between antipsychotics and diabetes. Lindenmayer et al 44 found clozapine, olanzapine, and haloperidol, but not risperidone, to be associated with an increase of plasma glucose level.…”
mentioning
confidence: 99%
“…Abnormalities in glucose regulation were first reported in schizophrenia before the introductionofantipsychoticmedications. 1,2 Phenothiazine treatment was subsequently observed to contribute to glucoregulatory abnormalities, [14][15][16][17][18] including reports of aggravation of existing diabetes 19 and newonset type 2 diabetes. [20][21][22] This association is not consistently found for all older antipsychotics, 23 with few reports implicating higher-potency agents like haloperidol.…”
mentioning
confidence: 99%